Effectiveness of copper and zinc supplementation in patients treated by nutrition therapy - Korczak, Maria; Grabowska, Urszula; Kozieł, Dorota; Głuszek, Stanisław (Medical Studies/Studia Medyczne, 2016)
Introduction: Parenteral nutrition (PN) therapy may be effective only provided that the organism is supplied with all the indispensable components. In clinical practice, the treatment of an undernourished patient requires the introduction of substitution of various nutrients, including such elements as copper and zinc. Aim of the research: An evaluation of the effectiveness of copper and zinc supplementation in patients receiving short-term parenteral nutrition therapy – lasting up to 10 days, and long-term therapy – for more than 10 days. Material and methods: The study was conducted in the Clinical Department of Surgery at the Regional Polyclinical Hospital in Kielce. Two study groups were distinguished: group 1 – PN with supplementation up to 10 days, into which were qualified 35 patients (16 females and 19 males; median age 66 years); group 2 – PN with supplementation lasting for more than 10 days, into which were qualified 34 patients (15 females and 19 males, median age 59 years), and two control groups. Control group 1 were 20 healthy individuals selected at random from among the medical staff. Control group 2 were patients qualified for planned surgical procedure of gallbladder removal. In order to evaluate the concentration of copper and zinc in patients in the study groups, venous blood was collected prior to the introduction of nutrition, and within 7-day intervals during the parenteral nutrition. Results: No statistically significant differences were observed between the concentrations of zinc in the blood of patients in study groups 1 and 2. This means that, irrespective of the time of measurement, the zinc concentration in blood was similar. In study group 1, the mean concentration of copper was higher in the measurement performed after 7 days of PN (88.48 µg/dl), compared to the measurement prior to PN (82.45 µg/dl) (p = 0.028). The lowest mean concentration of copper in blood in study group 2 was observed in the measurement prior to the introduction of PN (71.17 µg/dl) and, at the same time, it was lower than the measurements performed after 14 (98.16 µg/dl), 21 (96.33 µg/dl), and 28 (100.03 µg/dl) days. A significant increase in the concentration of copper and zinc was observed after 14 days of PN. Conclusions: based on the results of the analysis performed, it was found that zinc and copper administration in standard PN doses is sufficient. The concentration of copper remains within reference values; however, it is higher after PN therapy.